Observing cosmic reionization with PAPER: polarized foreground simulations and all sky images - Nunhokee, Chuneeta Devi (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2019)
The Donald C. Backer Precision Array to Probe the Epoch of Reionization (PAPER, Parsons et al., 2010) was built with an aim to detect the redshifted 21 cm Hydrogen line, which is likely the best probe of thermal evolution of the intergalactic medium and reionization of neutral Hydrogen in our Universe. Observations of the 21 cm signal are challenged by bright astrophysical foregrounds and systematics that require precise modeling in order to extract the cosmological signal. In particular, the instrumental leakage of polarized foregrounds may contaminate the 21 cm power spectrum. In this work, we developed a formalism to describe the leakage due to instrumental widefield effects in visibility-based power spectra and used it to predict contaminations in observations. We find the leakage due to a population of point sources to be higher than the diffuse Galactic emission "“ for which we can predict minimal contaminations at k>0.3 h Mpc -Â¹ We also analyzed data from the last observing season of PAPER via all-sky imaging with a view to characterize the foregrounds. We generated an all-sky catalogue of 88 sources down to a flux density of 5 Jy. Moreover, we measured both polarized point source and the Galactic diffuse emission, and used these measurements to constrain our model of polarization leakage. We find the leakage due to a population of point sources to be 12% lower than the prediction from our polarized model.
Keywords: Cosmic background radiation; Astronomy -- Observations; Epoch of reionization -- Research; Hydrogen -- Spectra; Radio interferometers